Edmund Anscombe (1874-1948): early competition work - McCarthy, Christine (Architectural History Aotearoa, 2004)
Edmund Anscombe is reputed to have begun his architectural career in Dunedin with the success of the University of Otago School of Mines competition, after spending five years in America (1902-1906) studying architecture. His early career is characterised by consistent success in architectural competitions over a short period of time. He won competitions for the University of Otago School of Mines (1908), the Young Men's Christian Association Building (1909), the Hanover Street Baptist Church (1910), and the Dunedin Girls' High School (1909) - where he won first and second place. This competition work chronologically culminates in an unsuccessful entry in the 1911 competition for a new New Zealand Parliament, which was won by John Campbell and Claude Paton.